High zirconia electrically fused cast refractory
Patent Information
- Application Number
- CN202380029308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2023-03-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-03-10
AI Technical Summary
[0041]文献8的耐火物有时产生龟裂,难以以生产水平制造
[0088] According to the present invention, improved high-zirconia electrofused cast refractories can be provided. In particular, if the high-zirconia electrofused cast refractories of the present invention, which are easily mass-produced industrially, are used in glass melting furnaces, the opening of seams at the contact points between refractories is suppressed. Furthermore, the formation of zircon crystals is suppressed; even if zircon crystals are formed, the residual volume expansion rate does not become extremely large, and cracking does not occur in the refractories. Therefore, refractories with high corrosion resistance to glass can be provided. Thus, long-term operation is possible, which is highly beneficial industrially.
Smart Images

Figure CN118922394B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to high-zirconia electro-cast refractories suitable for use in glass melting furnaces. Background Technology
[0002] As refractory materials for glass melting furnaces, electro-cast refractory materials (hereinafter sometimes simply referred to as "refractory materials") have been the most commonly used materials.
[0003] Electrofused cast refractories are made by melting raw materials, such as alumina, silicon dioxide, and zirconium oxide, with trace amounts of sodium carbonate and boric acid in a given amount in an electric arc furnace, casting the molten material in a refractory mold, and then cooling it together with the mold in an annealing material to solidify it into the mold shape. This process produces dense refractories with excellent corrosion resistance to molten glass.
[0004] Electrofused cast refractories are manufactured by casting molten material in a mold, which is different from the manufacturing method of sintered refractories, which are manufactured by sintering and bonding crystal particles. In addition, the technology, methods and solutions for sintered refractories cannot be used for electrofused cast refractories, and vice versa.
[0005] As one type of electro-cast refractories, high-zirconia electro-cast refractories containing more than 85% by mass of ZrO2 are generally used.
[0006] High-zirconia electrofused cast refractories have low solubility in glass and are mainly composed of ZrO2 with a high melting point. They have a high ZrO2 content and a dense structure, thus exhibiting great corrosion resistance to all types of molten glass.
[0007] Furthermore, high-zirconia electrofused cast refractories possess properties such as not forming a reaction layer at the interface with molten glass, thus exhibiting excellent characteristics such as difficulty in generating defects like nodules and streaks in molten glass.
[0008] Therefore, high-zirconia electrofused refractory is particularly suitable for manufacturing high-quality glass.
[0009] The mineral structure of high-zirconia electrofused cast refractories is characterized by a majority of monoclinic ZrO2 crystals occupying the crystal boundaries of the ZrO2 crystals, with a small amount of glassy phase filling the crystal boundaries of the ZrO2 crystals.
[0010] This small amount of glass phase is very different from the composition of glass used in the glass industry. It is a glass rich in SiO2. It is melted simultaneously with a high content of ZrO2 and then cast in a mold. Therefore, the technological development methods and solutions of the glass industry cannot be used for electrofused casting of refractory materials, and vice versa.
[0011] The glass phase of high zirconia electrofused cast refractories is generally composed of oxides such as Al2O3, SiO2, Na2O, B2O3, and P2O5.
[0012] Moreover, the ZrO2 crystals, which make up the majority of the high-zirconia electrofused cast refractories, undergo a reversible phase transition from monoclinic to tetragonal crystals due to the rapid volume change around 1000℃ (when cooling) to 1150℃ (when heating).
[0013] By employing the flow of a glassy phase filling the grain boundaries of ZrO2 crystals to mitigate the stress caused by the volume change accompanying the phase transformation of the ZrO2 crystals, it is possible to manufacture and sell high-zirconia electro-cast refractories with a ZrO2 content of 93–94% by mass that are free from cracks during manufacturing and heating.
[0014] However, the rapid volume change of the ZrO2 crystal from 1000℃ (during cooling) to 1150℃ (during heating), along with the reversible phase transition from monoclinic to tetragonal crystals, has a significant impact on glass melting furnaces when high-zirconia electrofused casting refractories are used in the glass industry.
[0015] That is, high-zirconia electrofused refractory expands upon heating, but transforms from monoclinic to tetragonal crystals in the ZrO2 phase transformation temperature region, accompanied by a sharp volume shrinkage. With further heating, the refractory expands, but its expansion does not exceed the maximum expansion of monoclinic crystals in the ZrO2 phase transformation temperature region within the operating temperature range of the glass melting furnace.
[0016] Therefore, for general high zirconia electrofused cast refractories, in the glass melting furnace in operation, a temperature distribution occurs between the inner side of the furnace, which is in contact with the molten glass and reaches the maximum temperature (generally 1300℃~1700℃), and the outer side of the glass melting furnace, which is in contact with the atmosphere (or insulation material), with maximum expansion between these two surfaces.
[0017] That is, when the temperature rises, the ZrO2 crystal shrinks due to the phase transformation from monoclinic to tetragonal crystal, which means that the refractory has a smaller expansion rate than the maximum expansion rate in the part of the furnace inside in contact with the molten glass.
[0018] In the part of the furnace inside that comes into contact with the molten glass, if the refractory has an expansion rate smaller than the maximum expansion, then in a glass melting furnace where refractory combinations are used, the part called the "seam" that serves as the contact point between the refractory combinations is slightly open.
[0019] If the contact area between the refractory materials, i.e. the joint, is open, the flow rate of the glass near the joint changes, thus accelerating the glass-induced erosion of the refractory.
[0020] In addition, regarding high zirconia electrofused cast refractories, if the refractories are heated alone, or subjected to thermal cycling in the temperature range of 1000℃ (during cooling) to 1150℃ (during heating) with ZrO2 crystals, where a rapid volume change occurs between monoclinic and tetragonal crystals, sometimes the main component of the glass phase of the refractories, namely silicon dioxide (SiO2), reacts with zirconia (ZrO2) crystals to form zircon (ZrO2·SiO2) crystals.
[0021] Under heating and thermal cycling, zircon crystals form at the interface between ZrO2 crystals and the glassy phase filling its crystal boundaries, or at the glassy phase itself. Therefore, the formation of zircon crystals leads to a relative reduction in the glassy phase. Furthermore, if the reduction in the glassy phase progresses due to the growth and increase of zircon crystals, the glassy phase becomes less able to absorb the rapid volume changes of ZrO2 crystals around 1000°C to 1150°C, resulting in reduced strength of the refractory and increased susceptibility to cracking.
[0022] At this point, selective erosion occurs from the cracked areas, and if the erosion progresses, crystals that constitute high-zirconia electrofused cast refractories are mixed into the molten glass, sometimes leading to a reduction in the quality of the glass.
[0023] Therefore, in the operation of glass melting furnaces, in order to achieve long-term stable operation and maintain stable glass quality, it is very important to suppress the formation of zircon crystals in high-zirconia electrofused casting refractories.
[0024] Therefore, so far, the research has focused on adding Y2O3 to refractory materials to suppress the opening of the joint at the contact point between refractory materials, also known as the "joint".
[0025] In addition, high-zirconium oxide electrofused cast refractories that suppress the formation of zircon crystals have been studied so far.
[0026] Patent document 1 proposes a heat-resistant mechanical material made of fused cast zirconia, characterized in that it comprises single crystals and / or polycrystalline materials having a composition expressed in mole percent as 89≦ZrO2≦99 and 1≦Y2O3≦11.
[0027] Regarding the refractory in Reference 1, although it does not contain SiO2 and therefore does not form zircon crystals, it also cannot absorb the rapid volume change during the phase transition from monoclinic to tetragonal ZrO2 crystals, making it difficult to mass-produce the refractory in industry.
[0028] Patent document 2 proposes a fused zirconia refractory material, characterized in that, as a stabilizer, it contains 1 to 30 wt% calcium oxide and 0.05 to 2 wt% yttrium oxide or a rare earth mineral containing yttrium oxide.
[0029] Regarding the refractory in Reference 2, although it does not produce zircon crystals due to the absence of SiO2, it cannot absorb the rapid volume change during the phase transition from monoclinic to tetragonal ZrO2 crystals, making it difficult to mass-produce the refractory in industry.
[0030] Patent document 3 discloses a product that is a refractory product containing more than 85% zirconium oxide (ZrO2), characterized in that, based on oxides, it contains ZrO2 > 92%, SiO2: 2-8%, Na2O: 0.12-1%, Al2O3: 0.2-2%, and 0.5% ≤ Y2O3 + CaO ≤ 2.6%, wherein Y2O3: 0.3-2%, or CaO: 0.5-1.93%.
[0031] Regarding the refractory in Reference 3, cracking occurs during production, making it difficult to manufacture at a production level. As explained below, this is believed to be due to the relatively low Y2O3 content.
[0032] Patent document 4 proposes a refractory that is melted and then cast into shape, wherein, expressed as a percentage by weight of oxides, the total is set to 100%, including ZrO2: 100% balance, Hf2O: <5%, SiO2: 2%~10%, 0.9 < Y2O3+CeO2+CaO+MgO≦4.0%, B2O3: ≦4.5%, and B2O3: ≧0.09×(Y 2O3+1 / 3(CeO2+CaO+MgO))×SiO2, Al2O3: 0.3%~2.0%, Na2O+K2O: ≦0.5%, P2O5: <0.05%, Fe2O3+TiO2: <0.55%, other species: <1.0%, of which Y2O3 content is above 0.5% or CeO2+CaO+MgO content is above 2%.
[0033] Regarding the refractory in Reference 4, it contains a large amount of CaO and MgO, which significantly promote the formation of zircon crystals. Due to the increased residual volume expansion after heating caused by the formation of zircon crystals, cracks may occur in the refractory, potentially reducing the strength of the refractory structure.
[0034] Patent document 5 proposes a castable refractory, which, expressed as a weight percentage based on oxides and relative to a total of 100%, comprises: ZrO2: balance up to 100%, Hf2O: <5%, SiO2: 2%–10%, Y2O3: 0.4%–2.0%, CaO: 4.0%–8.0%, B2O3+Na2O+K2O: 0.4%–3.0%, Al2O3: 0.3%–2.0%, P2O5: <0.05%, Fe2O3+TiO2: <0.55%, and other species: <1.5%.
[0035] In reference 5, a large amount of CaO is contained, which significantly promotes the formation of zircon crystals. The increased residual volume expansion after heating due to the formation of zircon crystals and anorthite crystals (CaAl2Si2O8) can cause cracking in the refractory and may reduce the strength of the refractory structure.
[0036] Patent document 6 proposes a refractory that is melted and then cast, wherein, expressed as a percentage by weight of oxides, the total is set to 100%, comprising: ZrO2: 100% balance; SiO2: 2%–10%; 0.9 < Y2O3 + CeO2 + CaO + MgO ≤ 4.0%; B2O3: ≤ 4.5%; B2O3: ≥ 0.09 × (Y2O3 + 1 / 3 (CeO2 + CaO + MgO)) × SiO2; Al2O3: 0.3%–2.0%; and Y2O3: ≥ 0.8%. The percentage of each of the following characteristics must be met: HfO2: <5%, CeO2: <0.7%, MgO: <0.7%, CaO: <0.7%, Na2O+K2O: ≦0.5%, P2O5: <0.05%, Fe2O3+TiO2: <0.55%, and the amount of each of the species other than ZrO2, HfO2, SiO2, Y2O3, CeO2, CaO, MgO, B2O3, Al2O3, Na2O, K2O, P2O5, Fe2O3, and TiO2: <0.2%.
[0037] Regarding the refractory in Reference 6, cracking occurs during production, making mass production of the refractory industrially difficult. As explained below, this is believed to be due to the Y2O3 content being below 4%.
[0038] Patent document 7 proposes a high-zirconia electro-cast refractories, wherein ZrO2 comprises 85–95% by weight, Al2O3 comprises 0.4–2.5% by weight, SiO2 comprises 3.5–10% by weight, the total amount of Na2O and K2O comprises 0.05–1% by weight, B2O3 comprises more than 0.04% by weight and less than 1% by weight, P2O5 comprises less than 0.02% by weight, MgO comprises less than 0.05% by weight, and CaO comprises less than 1% by weight. The content is 0.01 to 0.2% by weight. When SrO and BaO are contained individually, SrO is 0.3 to 3% by weight or BaO is more than 0.5% by weight and less than 3% by weight. When both are contained, SrO is more than 0.3% by weight. The total content of SrO and BaO is 0.3 to 3% by weight. SnO2 is 0.01 to 0.7% by weight. The total content of Fe2O3 and TiO2 is less than 0.3% by weight.
[0039] The refractory in Reference 7 has an extremely low Y2O3 content, so it cannot suppress the opening of the joint, and the corrosion resistance of the joint is insufficient.
[0040] Patent document 8 proposes a castable refractory product, expressed as a mass percentage based on oxides and relative to the total of 100% of oxides, comprising ZrO2 + HfO2: up to 100% balance, wherein Hf2O ≦5%, SiO2: 1.5%–7.5%, Al2O3: 1.0%–3.0%, CaO + SrO: 1.2%–3.0%, Y2O3: 1.5%–3.0%, Na2O + K2O: <0.15%, B2O3: <1.0%, P2O5: <0.15%, Fe2O3 + TiO2: <0.55%, and oxides other than ZrO2, HfO2, SiO2, Al2O3, Na2O, K2O, B2O3, CaO, SrO, Y2O3, P2O5, Fe2O3, and TiO2: <1.5%.
[0041] The refractory in Reference 8 sometimes cracks, making it difficult to manufacture at a production level. As explained below, this is believed to be because the Y2O3 content is below 4%.
[0042] Existing technical documents
[0043] Patent documents
[0044] Patent Document 1: Japanese Patent Application Publication No. 59-131585
[0045] Patent Document 2: Japanese Patent Application Publication No. 4-42813
[0046] Patent Document 3: Japanese Patent Publication No. 2005-526683
[0047] Patent Document 4: Japanese Patent Publication No. 2013-514254
[0048] Patent Document 5: Japanese Patent Publication No. 2015-506898
[0049] Patent Document 6: Japanese Patent Application Publication No. 2015-212223
[0050] Patent Document 7: Japanese Patent Application Publication No. 2015-40144
[0051] Patent Document 8: Japanese Patent Publication No. 2018-509363 Summary of the Invention
[0052] The problem that the invention aims to solve
[0053] Generally, if high-zirconia electrofused cast refractories contain Y₂O₃, most of the Y₂O₃ will be dissolved in the ZrO₂ crystal, and a portion will be contained in the glassy phase of the refractories. In this case, through the solid solution of Y₂O₃ in the ZrO₂ crystal, a portion becomes tetragonal ZrO₂, changing the properties of the ZrO₂ crystal. Specifically, the phase transition temperature of the reversible crystal phase from monoclinic to tetragonal, accompanied by a rapid volume change in the ZrO₂ crystal from approximately 1000℃ (during cooling) to 1150℃ (during heating), and therefore the maximum expansion temperature, shifts towards the lower temperature side.
[0054] On the other hand, as mentioned above, regarding the refractory during operation, a temperature distribution occurs between the inner surface of the glass melting furnace that is in contact with the molten glass and the outer surface of the glass melting furnace that is in contact with the atmosphere (or insulation material). Typical high-zirconia electrofused cast refractories exhibit maximum expansion between these two surfaces. If the phase transformation temperature of the ZrO2 crystal shifts towards a lower temperature, the maximum expansion of the refractory moves in the direction of the outer surface of the glass melting furnace that is in contact with the atmosphere (or insulation material). Compared to typical refractories, at lower temperatures, the ZrO2 crystal undergoes a phase transformation to tetragonal crystals and then expands. Therefore, the expansion of the inner surface of the glass melting furnace in contact with the molten glass is the same as or slightly smaller than the maximum expansion of the refractory, causing the joints that are the contact points between the refractories to close or suppress the opening of the joints.
[0055] However, if the phase transition temperature of the ZrO2 crystal phase shifts to the lower temperature side, the viscosity of the glass phase is high on the lower temperature side, which is the temperature range for the glass phase to solidify. Therefore, the glass phase cannot alleviate the stress caused by the volume change accompanying the phase transition of the ZrO2 crystal, and is prone to cracking. This may make it difficult to mass-produce refractory materials in industry.
[0056] Furthermore, if the phase transformation temperature of the ZrO2 crystal phase shifts to a lower temperature side to a greater extent, it will no longer be possible to further mitigate the stress caused by the volume change accompanying the phase transformation of the ZrO2 crystal during refractory manufacturing, which may also promote the occurrence of cracks.
[0057] Therefore, it is considered difficult to increase the Y2O3 content, increase the migration of the ZrO2 crystal phase phase transformation temperature to the lower temperature side, and thus manufacture high-quality zirconia electrofused cast refractories.
[0058] Furthermore, when using refractory materials in glass melting furnaces where the phase transformation temperature of the ZrO2 crystal phase shifts towards the lower temperature side, if zircon crystals are formed during operation, the glass phase becomes relatively reduced. Moreover, the viscosity of the glass phase is high at low temperatures, leading to solidification of the glass phase on the lower temperature side. Therefore, if thermal cycling occurs due to temperature changes during glass melting furnace operation, it becomes less able to absorb the rapid volume changes of ZrO2 crystals compared to general high-zirconia electrofused cast refractory materials, which may easily lead to cracking.
[0059] Therefore, it is believed that high-zirconia electro-casting refractories, which have a relatively higher Y2O3 content, are not suitable for use in the parts of glass melting furnaces where thermal cycling occurs due to temperature changes.
[0060] Furthermore, if the Y2O3 content is increased, the ZrO2 content decreases relatively. The ZrO2 content has a significant impact on the corrosion resistance of refractory materials relative to glass. Since the corrosion resistance of refractory materials is proportional to the ZrO2 content, refractory materials with relatively low ZrO2 content are considered to have insufficient corrosion resistance.
[0061] Therefore, it is believed that high-zirconia electrofused refractory materials with increased Y2O3 content sometimes do not have sufficient corrosion resistance in glass melting furnaces.
[0062] Against this backdrop, the objective of this invention is to provide improved high-zirconia electrofused cast refractories, and more particularly, to provide high-zirconia electrofused cast refractories that are easy to mass-produce industrially, suppress the opening of the seams at the contact points between refractories, i.e., the "joints," and further suppress the formation of zircon crystals. Even if some zircon crystals are formed, the residual volume expansion rate will not increase drastically. The refractories do not crack when subjected to heating and thermal cycling, and exhibit high corrosion resistance to glass.
[0063] Methods for solving problems
[0064] If we exemplify the solution of the present invention, it is the following high-zirconia electro-cast refractory.
[0065] <Option 1>
[0066] The high-zirconia electrofused cast refractories contain the following chemical composition: the total content of ZrO2 and HfO2 is greater than 80% and less than 92% by mass; Al2O3 is 0.2% to 3.0% by mass; SiO2 is 1.5% to 10% by mass; Na2O is 0.05% to 2.0% by mass; K2O is less than 1.0% by mass; B2O3 is 0% to 1.5% by mass; Y2O3 is greater than 4.0% and less than 9.0% by mass; the total content of MgO and CaO is 0.02% to 0.4% by mass; CaO is greater than 0.01% by mass; the total content of Fe2O3 and TiO2 is less than 0.5% by mass; and P2O5 content is less than 0.04% by mass.
[0067] <Option 2>
[0068] According to Scheme 1, the high-zirconia electrofused cast refractory comprises, as a chemical composition, ZrO2 and HfO2 totaling more than 80% by mass and less than 92% by mass, Al2O3 of 0.4 to 2.5% by mass, SiO2 of 1.5 to 7.0% by mass, Na2O of 0.3 to 1.8% by mass, K2O of less than 1.0% by mass, B2O3 of 0 to 1.0% by mass, Y2O3 of more than 4.0% by mass and less than 7.5% by mass, MgO and CaO totaling 0.02 to 0.4% by mass, CaO of more than 0.01% by mass, Fe2O3 and TiO2 totaling less than 0.5% by mass, and P2O5 content of less than 0.04% by mass.
[0069] <Option 3>
[0070] According to Scheme 1 or 2, the high zirconium oxide electrofused cast refractory contains Y2O3 with a mass content of 4.5 to 7.5%.
[0071] <Option 4>
[0072] According to Scheme 3, the high zirconium oxide electrofused cast refractory contains Y2O3 with a mass content of more than 4.5% by mass and less than 6.0% by mass.
[0073] <Option 5>
[0074] According to any one of Schemes 1 to 4, the high zirconium oxide electrofused cast refractories contain SiO2 with a mass content of 4.0 to 6.5%.
[0075] <Option 6>
[0076] According to any one of Schemes 1 to 5, the high-zirconia electrofused cast refractories contain Al2O3 with a mass content of 0.5 to 1.2%.
[0077] <Option 7>
[0078] According to any one of Schemes 1 to 6, the high zirconium oxide electrofused cast refractories contain Na2O with a mass content of 0.5 to 1.2%.
[0079] <Option 8>
[0080] According to any one of Schemes 1 to 7, the high zirconium oxide electrofused cast refractories contain B2O3 with a mass content of 0.01 to 0.6% (by mass).
[0081] <Option 9>
[0082] According to any one of Schemes 1 to 8, the high zirconia electrofused cast refractory, wherein the refractory's expansion rate reaches its maximum at temperatures between 1300°C and 1500°C during the heating process from 200°C to 1500°C.
[0083] <Option 10>
[0084] According to any one of Schemes 1 to 9, the high zirconium oxide electrofused cast refractory, wherein during the cooling process from 1500°C, the ZrO2 crystals do not shrink from the tetragonal phase to the monoclinic phase.
[0085] <Option 11>
[0086] The high zirconia electro-casting refractory according to any one of Schemes 1 to 10 is used in a glass melting furnace.
[0087] The effects of the invention
[0088] According to the present invention, improved high-zirconia electrofused cast refractories can be provided. In particular, if the high-zirconia electrofused cast refractories of the present invention, which are easily mass-produced industrially, are used in glass melting furnaces, the opening of seams at the contact points between refractories is suppressed. Furthermore, the formation of zircon crystals is suppressed; even if zircon crystals are formed, the residual volume expansion rate does not become extremely large, and cracking does not occur in the refractories. Therefore, refractories with high corrosion resistance to glass can be provided. Thus, long-term operation is possible, which is highly beneficial industrially. Attached Figure Description
[0089] Figure 1 The graph shows the thermal expansion coefficient determination of the high zirconia electrofused cast refractories with 93% by mass (0.24% by mass Y2O3 content) and the components involved in Examples 2 and 8.
[0090] Figure 2 The graph shows the thermal expansion coefficient determination of the high zirconia electrofused cast refractories with 93% by mass (0.24% by mass Y2O3 content) and Comparative Example 16.
[0091] Figure 3 A diagram of the apparatus used in the evaluation of corrosion resistance.
[0092] Figure 4 A photograph of the appearance of the sample after the corrosion resistance evaluation.
[0093] Figure 5A Photograph of the internal structure of a high-zirconia electrofused cast refractories with 93% by mass (0.24% by mass Y2O3 content) after corrosion resistance evaluation.
[0094] Figure 5B Photographs of the internal structure of the high zirconia electrofused cast refractories involved in Example 1 after evaluation of corrosion resistance. Detailed Implementation
[0095] Through in-depth research, the inventors of this application discovered that in refractory materials where the combined content of ZrO2 and HfO2 exceeds 80% but is less than 92% by mass, the problem of this invention can be solved by adjusting the contents of each component—Al2O3, SiO2, Na2O, K2O, B2O3, MgO, CaO, P2O5, Fe2O3, and TiO2—within specific ranges, thereby ensuring that the Y2O3 content exceeds 4% but is less than 9% by mass. Specifically, it was found that with this composition, the ZrO2 crystal phase can be transformed into a tetragonal crystal, not only partially but entirely. As a result, the reversible phase transition from monoclinic to tetragonal ZrO2 crystals almost disappears, and the abrupt volume change also disappears. Furthermore, it was found that during the heating process from 200°C to 1500°C, if the temperature at which the expansion rate of the refractory reaches its maximum is between 1300°C and 1500°C, the maximum expansion area that previously existed between the outer side and the inner side of the furnace in high zirconia electrofused cast refractory can be moved to the inner side of the furnace in contact with the molten glass. Therefore, at the contact area between refractory materials, the joint opening is completely or substantially completely suppressed.
[0096] That is, by making the Y₂O₃ content between 4% and 9% by mass, the reversible phase transition from monoclinic to tetragonal ZrO₂ disappears or largely disappears. Therefore, even if the phase transition temperature of the ZrO₂ phase shifts to a lower temperature side, the stress generated by the volume change accompanying the phase transition of the ZrO₂ crystal is small or largely disappears. Thus, cracking can be suppressed during refractory manufacturing, making mass production in industry easier. It also suppresses the opening of seams in refractory used in glass melting furnaces, increasing the corrosion resistance of glass. Furthermore, for such refractory, the ZrO₂ crystal does not shrink from the tetragonal phase to the monoclinic phase during the cooling process from 1500℃. Therefore, it was found that when zircon crystals are generated during heating and thermal cycling in glass melting furnace operations, the reversible phase transformation between monoclinic and tetragonal ZrO2 phases disappears or largely disappears during the heating and cooling processes. Thus, it is possible to provide high zirconium oxide electrofused cast refractories that do not crack in the refractories.
[0097] Furthermore, it was found that increasing the Y₂O₃ content relatively decreases the ZrO₂ concentration. Through the solid solution of Y₂O₃ in ZrO₂, Y₂O₃ plays a role roughly equivalent to ZrO₂, exhibiting corrosion resistance comparable to conventional high-zirconia electrofused cast refractories with a ZrO₂ content of 93–94% by mass. Alternatively, high-concentration Y₂O₃ nodules are formed by the crystallization of a portion of the Y₂O₃ contained in the glass phase during heating, or by the dissolution of Y₂O₃ dissolved in ZrO₂ into the glass phase. These nodules facilitate the formation of a three-dimensional network between ZrO₂ particles, thus improving corrosion resistance (see reference). Figure 5B ).
[0098] Ingredients
[0099] The components of the refractory involved in this invention are described below. "Substantially free of" means less than 0.01% by mass.
[0100] <ZrO2>
[0101] The ZrO2 content in high-zirconia electrofused cast refractories can be relatively determined based on the content of other components. However, if the ZrO2 content is too high, the content of other components will relatively decrease.
[0102] Furthermore, the ZrO2 and zircon raw materials used as raw materials for high-zirconia electrofused cast refractories inevitably contain 1-2% by mass of HfO2. HfO2 does not volatilize during manufacturing and is therefore also included in the high-zirconia electrofused cast refractories. Moreover, as a stable oxide similar to ZrO2, it has the same effect as ZrO2, therefore the ZrO2 + HfO2 content can also be treated as the ZrO2 content.
[0103] Therefore, the total content of ZrO2 and HfO2 in this invention is more than 80% by mass and less than 92% by mass, preferably 81-92% by mass, 82-92% by mass, 83-92% by mass, 84-92% by mass, 85-92% by mass, 86-92% by mass, and more preferably 86-91% by mass, 86-90% by mass, and 86-89% by mass.
[0104] <SiO2>
[0105] SiO2 is the main component of the glass phase in the refractory of this invention.
[0106] The SiO2 content is 1.5–10% by mass. More preferably, it is 1.5–9.0% by mass, 1.5–8.0% by mass, or 1.5–7.0% by mass. Even more preferably, it is 2.0–7.0% by mass, 3.0–7.0% by mass, 4.0%–7.0% by mass, 4.0%–6.5% by mass, or 4.0–6.0% by mass.
[0107] Even though the solid solution of Y₂O₃ in ZrO₂ crystals results in almost no shrinkage during the phase transition from monoclinic to tetragonal, shrinkage can still occur during this phase transition. In such cases, if the SiO₂ content is less than 1.5% by mass, the amount of glassy phase formed is reduced, failing to completely suppress the stress generated by the volume change accompanying the ZrO₂ phase transition, making cracking more likely. If the SiO₂ content exceeds 10% by mass, the ZrO₂ content decreases relatively, sometimes resulting in reduced corrosion resistance.
[0108] <Al2O3>
[0109] Regarding Al2O3, in this invention, even without its direct addition, it has almost no impact on industrial mass production. However, Al2O3 has the effect of suppressing the formation of zircon crystals, so it is preferred to contain it. However, if it exceeds 2.5% by mass, corundum and mullite crystals tend to precipitate in the glass phase during manufacturing and heating. But even if crystals precipitate, the phase transformation from monoclinic to tetragonal crystal phase disappears or substantially disappears through the solid solution of Y2O3 in ZrO2 crystals. Therefore, even if these products, which cause cracking during the manufacture of high-zirconia electrofused cast refractories, are present, they have almost no impact on industrial mass production.
[0110] In this invention, the Al2O3 content is 0.2 to 3.0% by mass. Since Al2O3 exists as an impurity in ZrO2 and SiO2 raw materials, it generally contains more than 0.2% by mass even without being newly added. Furthermore, if it exceeds 3.0% by mass, it relatively leads to a decrease in ZrO2 content, sometimes resulting in reduced corrosion resistance.
[0111] Therefore, the content of Al2O3 is 0.2 to 3.0% by mass, more preferably 0.3 to 3.0% by mass, 0.3 to 2.5% by mass, 0.4 to 3.0% by mass, or 0.4 to 2.5% by mass, and even more preferably 0.4 to 2.0% by mass, 0.4 to 1.5% by mass, 0.5 to 1.5% by mass, or 0.5 to 1.2% by mass.
[0112] <Na2O>
[0113] Na₂O functions as a modifying oxide in the glassy phase. It is an essential component for reducing the viscosity of the glassy phase, minimizing cracking during the manufacture of high-zirconia electrofused cast refractories, and facilitating industrial mass production. Additionally, Na₂O significantly inhibits the formation of zircon crystals in the glassy phase of refractories; however, if its content exceeds 2.0% by mass, the softening point of the glassy phase decreases significantly, making the refractories prone to deformation and sometimes reducing corrosion resistance.
[0114] Therefore, the Na2O content is 0.05–2.0% by mass, more preferably 0.2–2.0% by mass, 0.2–1.8% by mass, 0.3–1.8% by mass, 0.4–1.8% by mass, and even more preferably 0.5–1.7% by mass, 0.6–1.7% by mass, 0.7–1.7% by mass, or 0.5–1.4% by mass, 0.5–1.2% by mass, 0.5–1.0% by mass.
[0115] <K2O>
[0116] The K2O content is 1.0% by mass or less, preferably 0.5% by mass or less, more preferably 0.1% by mass or less, and particularly preferably substantially non-existent. "Substantially non-existent" means less than 0.01% by mass. There is no particular limitation on the lower limit of the K2O content; it can be 0.001% by mass or 0.0001% by mass.
[0117] <B2O3>
[0118] Regarding B2O3, even its absence in this invention has almost no impact on industrial mass production. However, even at low concentrations, B2O3 can suppress cracking during manufacturing, sometimes facilitating industrial mass production. On the other hand, if the content exceeds 1.5% by mass, the ZrO2 content decreases relatively, thus sometimes reducing the corrosion resistance of high-zirconia electrofused refractories. Furthermore, excessively high content can sometimes facilitate the formation of zircon crystals.
[0119] Therefore, the content of B2O3 is 0 to 1.5% by mass, more preferably 0 to 1.2% by mass, 0 to 1.0% by mass, and even more preferably 0.01 to 0.8% by mass, 0.01 to 0.6% by mass, more than 0.01% by mass but less than 0.58% by mass, 0.01 to 0.5% by mass, or 0.01 to 0.4% by mass, 0.01 to 0.2% by mass.
[0120] <Y2O3>
[0121] Y₂O₃ is the most important component in this invention. It is believed that by maintaining a Y₂O₃ content exceeding 4% by mass and below 9% by mass, the ZrO₂ crystal phase is transformed into a tetragonal phase, not just partially, but entirely or substantially entirely. This essentially eliminates the reversible phase transition between monoclinic and tetragonal ZrO₂ crystals, thus largely eliminating the abrupt volume change during the monoclinic-tetragonal phase transition. This results in suppression of cracking during manufacturing, facilitating mass production in industry. However, excessive Y₂O₃ content leads to the stabilization of cubic ZrO₂, potentially causing cracking during manufacturing. Conversely, insufficient Y₂O₃ content increases the proportion of monoclinic ZrO₂ compared to tetragonal ZrO₂, resulting in a larger abrupt volume change during the monoclinic-tetragonal phase transition, which can also contribute to cracking during manufacturing.
[0122] Therefore, the Y2O3 content is more than 4.0% by mass and less than 9.0% by mass, more preferably more than 4.0% by mass and less than 8.5% by mass, more than 4.0% by mass and less than 8.0% by mass, more than 4.0% by mass and less than 7.5% by mass, and even more preferably 4.5 to 7.5% by mass, 4.5 to 7.0% by mass, 4.5 to 6.5% by mass, 4.5 to 6.0% by mass, more than 4.5% by mass and less than 6.0% by mass, or 5.0 to 6.0% by mass.
[0123] <MgO>
[0124] MgO exists as an impurity in ZrO2 raw materials, so careful consideration is needed when selecting raw materials. Furthermore, a high MgO content can sometimes facilitate the formation of zircon crystals. In this invention, it is unnecessary to add MgO; preferably, it is 0.1% by mass or less, and more preferably, it is essentially non-existent.
[0125] <CaO>
[0126] In the case of CaO, its presence in a certain amount reduces the viscosity of the molten material in high-zirconia electrofused cast refractories, forming a stable glassy phase. Without it, the material becomes a highly unstable glassy phase, leading to cracking during manufacturing. This cracking makes mass production impossible. Therefore, the presence of CaO is essential.
[0127] Furthermore, the presence of CaO as a raw material for ZrO2 and zircon as a source of ZrO2 results in impurities. Therefore, to achieve a content of less than 0.01% in the refractory, high-purity reagents are required as raw materials, which are very expensive and unsuitable for mass production. Thus, a content of 0.01% by mass or more, preferably 0.02% by mass or more, is preferred. However, if the content exceeds a certain amount, it promotes the formation of zircon crystals, which requires caution. Since the reversible phase transition from monoclinic to tetragonal ZrO2 crystals almost disappears, even if zircon crystals are formed, it can be said that cracking will not occur in the refractory. However, in this invention, although the shrinkage rate is small, since the refractory also contains shrinkage due to the phase transition from monoclinic to tetragonal ZrO2 crystals, it is necessary to suppress the formation of zircon crystals.
[0128] Therefore, the CaO content is preferably 0.02% to 0.3% by mass, more preferably 0.02% to 0.2% by mass, or 0.02% to 0.1% by mass, and particularly preferably 0.03% to 0.2% by mass, or 0.03% to 0.1% by mass.
[0129] In addition, the total content of MgO and CaO is 0.02 to 0.4% by mass, preferably 0.02 to 0.35% by mass.
[0130] <Fe2O3 and TiO2>
[0131] Fe2O3 and TiO2 are impurities in ZrO2 and zircon raw materials. These oxides contribute to the coloring and foaming of molten glass, therefore their content needs to be limited. The combined content of Fe2O3 and TiO2 is 0.5% by mass or less, preferably 0.3% by mass or less, and more preferably 0.2% by mass or less. There is no particular limitation on the lower limit; the combined content of Fe2O3 and TiO2 can be 0.01% by mass or more.
[0132] <P2O5>
[0133] P2O5 is one of the components of glass and has the effect of producing low-melting-point glass and adjusting the viscosity of the melt during the manufacture of high-zirconia electrofused cast refractories. If P2O5 is present, it significantly promotes the formation of zircon crystals. Therefore, the refractories of the present invention are preferably substantially free of P2O5. Thus, the P2O5 content is preferably 0.04% by mass or less, more preferably 0.02% by mass or less.
[0134] Expansion rate (thermal expansion rate) of refractory materials
[0135] The expansion rate of refractory materials can be evaluated, for example, in a temperature range of 200°C to 1500°C, by the expansion rate during a heating process at each temperature of 100°C. Alternatively, in a temperature range of 1500°C to 300°C, the expansion rate can be evaluated by the expansion rate during a cooling process of 300°C.
[0136] During the heating process from 200°C to 1500°C, if the temperature at which the expansion rate of the refractory reaches its maximum is within the range of 1300°C to 1500°C, then the maximum expansion portion between the outer surface and the inner surface of the high-zirconia electrofused cast refractory in the prior art can be located on the inner surface of the furnace in contact with the molten glass. Therefore, at the contact portion between the refractory components, the seam opening can be completely or substantially completely suppressed. Thus, during the heating process from 200°C to 1500°C, it is preferable that the temperature at which the expansion rate of the refractory reaches its maximum is within the range of 1300°C to 1500°C.
[0137] Furthermore, regarding the expansion rate of the refractory during the cooling process, it is preferable that the ZrO2 crystal does not transform into a monoclinic crystal and instead shrinks. When the ZrO2 crystal transforms from a tetragonal phase to a monoclinic phase, a rapid volume expansion occurs. Therefore, in the case of zircon crystal formation, the relative reduction in the glassy phase makes it difficult for the glassy phase to absorb this rapid volume expansion, thus reducing the strength of the refractory and contributing to cracking. Therefore, during the cooling process from 1500℃ to 300℃, it is preferable that the refractory's expansion rate reaches its maximum between 1200℃ and 1500℃. It is believed that under these conditions, the phase transformation of ZrO2 crystals from tetragonal to monoclinic does not occur or is suppressed.
[0138] According to a preferred embodiment of the refractory material of the present invention, during a cooling process (cooling process) from 1500°C, the ZrO2 crystals do not shrink from a tetragonal phase to a monoclinic phase. This can be confirmed by the absence of an increase in the expansion rate corresponding to the phase transition from tetragonal to monoclinic when the expansion rate of the refractory during the cooling process (cooling process) from 1500°C is measured at 300°C per unit area.
[0139] The expansion rate (linear expansion rate) of the refractory during the heating and cooling processes can be measured separately according to JIS R 2207-3, in samples taken from the refractory using a diamond drill bit, using a thermomechanical analysis device (e.g., NETZSCH TMA4000SA).
[0140] Example
[0141] A preferred embodiment of the high-zirconia electrofused cast refractories according to the present invention will be described. It should be noted that the present invention is not limited to these embodiments.
[0142] Examples 1-14, Comparative Examples 15-24
[0143] The refractory materials involved in Examples 1 to 14 and Comparative Examples 15 to 24 were manufactured respectively, and their physical properties were evaluated.
[0144] <Manufacturing of Refractory Materials>
[0145] The ZrO2 raw material obtained by desilication of zirconium sand is mixed with oxide raw materials such as SiO2, Al2O3, Na2O, B2O3, and Y2O3, as well as nitrate raw materials, in a specified proportion based on oxide conversion. This mixture is then melted in an electric arc furnace. After a specified melting time, it is cast in a mold and submerged in a slowly cooling material along with the mold, allowing it to cool slowly to room temperature.
[0146] As for the mold, a graphite mold was used, with the product part measuring 100mm×300mm×300mm, and its upper part integrally connected to a riser part with an inner size of 140mm×235mm×350mm.
[0147] After slow cooling, the mold and casting are removed from the slowly cooling silica sand, and the mold is then separated from the casting. Regarding the casting, the product portion is cut away from the riser to obtain the desired high-zirconia electrofused cast refractories.
[0148] <Evaluation>
[0149] The refractory materials of Examples 1-14 and Comparative Examples 15-24 were evaluated for their physical properties as described below. Table 1 shows the composition and characteristics of the high-zirconia electrofused cast refractory materials of Examples 1-14, and Table 2 shows the expansion rates during the heating and cooling processes. Table 3 shows the composition and characteristics of the high-zirconia electrofused cast refractory materials of Comparative Examples 15-24, and Table 4 shows the expansion rates during the heating and cooling processes. The component quantities in Tables 1 and 3 are in mass percent (%).
[0150] <Component Analysis>
[0151] The analysis of each component was performed using wavelength dispersive X-ray fluorescence analysis. It should be noted that the B2O3 content was analyzed using high-frequency inductively coupled plasma optical emission spectrometry. However, this invention is not limited to these analytical methods, and other analytical methods can also be used.
[0152] <Cracks>
[0153] Regarding cracking during manufacturing, first observe the condition of the product after it has been removed from the slowly cooling material. Then, cut the product in half and observe its internal condition, evaluating it according to the following criteria.
[0154] +++: Refractory material with no cracks on the surface and inside, or with no cracks on the surface and internal cracks less than 50 mm in length.
[0155] ++: Refractory material with no surface cracks but internal cracks longer than 50mm.
[0156] +: Refractory material with surface cracks extending to both sides and internal cracks exceeding 50mm in length.
[0157] -: Refractory with surface cracks extending to more than three sides, or refractory that cracks upon removal from slowly cooling material.
[0158] <Bulk density and porosity>
[0159] Regarding bulk density and porosity, a 23mm diameter core was taken from the part 50mm from the bottom of the mold contact area and 50mm from the side of the mold contact area of the 300mm×300mm surface. The bulk density and apparent porosity of the sample with an internal length of 90mm and 5mm from the surface of the casting were calculated using the Archimedes method.
[0160] The preferred bulk density of the refractory is 5.10 g / cm³. 3 ~5.70g / cm 3 The range is specified. Additionally, the porosity of the refractory is preferably 5.00% or less or 3.00% or less (there is no particular limitation on the lower limit of porosity, it can be 0.80%).
[0161] <Expansion Rate (Temperature Expansion Rate)>
[0162] The expansion rate (linear expansion rate) of the refractory was measured according to JIS R 2207-3. For the samples used to evaluate the expansion rate of the refractory, a 5mm diameter core was cut from a position 20mm from the bottom of the mold contact portion of the 300mm×300mm face and 130mm from the side of the mold contact portion. A 40mm section was cut from each casting surface to create a sample with a central length of 20mm. The expansion rate was measured using a thermomechanical analysis device in the samples removed from the refractory. Results relating to Examples 1-14 and Comparative Examples 15-24 are shown in Tables 2 and 4, respectively. Furthermore, in Figure 1 The results of thermal expansion coefficient determinations for high-zirconia electro-cast refractories with 93% by mass (0.24% by mass Y₂O₃ content) and Examples 2 and 8 are shown. Figure 2 The results of the thermal expansion coefficient determination are shown for a high zirconia electrofused cast refractories of 93% by mass (0.24% by mass Y2O3 content) and Comparative Example 16.
[0163] <Corrosion Resistance>
[0164] A 22mm diameter core was cut from the bottom and side surfaces of the 300mm×300mm mold contact area, respectively, at positions of 50mm. A 5mm section was then cut from the surface of the casting, and the 90mm long section in the center was used as a sample for evaluating corrosion resistance.
[0165] exist Figure 3 The diagram shows the apparatus used in the evaluation of corrosion resistance. The evaluation of corrosion resistance was performed using alkali-free glass, as described below. The composition of the alkali-free glass used in this test was 62% by mass of SiO2, 16% by mass of Al2O3, 2% by mass of B2O3, 9% by mass of CaO, 9% by mass of SrO2, and 9% by mass of BaO.
[0166] <Corrosion Resistance Test Using Alkali-Free Glass>
[0167] Holes were machined into the alumina conduit for both the evaluation sample and the fixed sample. Refractory pins were inserted, and the evaluation sample was fixed to the alumina conduit. The refractory pins were then secured to the alumina conduit using a heat-resistant adhesive. One end of the alumina conduit was connected to the evaluation sample, and the other end was connected to the testing apparatus.
[0168] It will be filled with alkali-free glass ( Figure 3 The crucible for high zirconium oxide electroforming refractories (see attached figure 2) Figure 3 (See attached figure 3) After raising the temperature to 1700℃, the test apparatus connected to the alumina conduit is started, and the sample being evaluated is rotated at 40 rpm. The sample rotating at 40 rpm... Figure 3 (See attached figure 1) and alkali-free glass heated to 1700°C ( Figure 3 (See attached figure 2) Contact. The alkali-free glass was contacted with the evaluation sample at 1700°C for 168 hours. Then, the sample was removed from the refractory crucible, and the glass adhering to the evaluation sample was removed.
[0169] The amount of erosion was determined using vernier calipers at the most glass-eroded part of the extracted sample. Figure 4 The sample shown has a ZrO2 content of 93% by mass (Y2O3 content of 0.24% by mass). Figure 4 (Ref. 4) and the sample involved in Example 1 ( Figure 4 The appearance after the corrosion resistance test (see attached figure 5).
[0170] For comparison, the erosion amount of high zirconia electrofused cast refractories with a ZrO2 content of 93% by mass (Y2O3 content of 0.24% by mass) was used as the standard erosion amount, and the following standard was used for evaluation.
[0171] ++: Less erosion compared to the standard
[0172] +: Erosion level is the same as standard.
[0173] -: More erosion compared to the standard
[0174] For the refractory with a ZrO2 content of 93% by mass (Y2O3 content of 0.24% by mass) and the refractory involved in Example 1, internal microstructure photographs were taken after corrosion resistance evaluation. Figure 5A and Figure 5B Each photo is shown in the image.
[0175] <Residual volume expansion rate after thermal cycling test>
[0176] A 45mm diameter drill core was cut from the bottom and sides of the 300mm×300mm mold contact area, respectively, at positions of 50mm. 25mm sections were cut from the surface of each casting, and the central 50mm section was used as the evaluation sample.
[0177] The sample was heated to 600°C at a rate of 3°C / min and held for 1 hour. Then, it was heated to 1450°C at a rate of 3°C / min and held for 1 hour. After holding for 1 hour, it was cooled to 600°C at a rate of 3°C / min and held for 1 hour. This cycle of holding at 600°C for 1 hour and at 1450°C for 1 hour constituted one thermal cycle, and was repeated 20 times. After 20 thermal cycles, the residual volume expansion rate was calculated based on the volume difference of the evaluation sample measured before and after heating.
[0178] The calculated residual volume expansion rate is preferably below 2%, more preferably below 1%. If the residual volume expansion rate exceeds 5%, pulverization of a portion of the sample begins, which is not preferred; if it exceeds 10%, the entire sample begins to pulverize, which is even less preferred.
[0179] Evaluation Results
[0180] Examples 1-14 are refractory materials with a Y₂O₃ content exceeding 4% by mass. See Table 2 (and...). Figure 1 As seen in the previous examples, during the heating process from 200°C to 1500°C, the temperature at which the expansion rate of the refractory reaches its maximum is within the range of 1300°C to 1500°C in Examples 1 to 14. Furthermore, during the cooling process from 300°C to 1500°C, the temperature at which the expansion rate of the refractory reaches its maximum is above 1200°C in Examples 1 to 14. No abrupt volume change near the phase transition temperature of the ZrO2 crystal phase was observed in Examples 1 to 14. This indicates that in the refractory examples 1 to 14, the reversible phase transition from monoclinic to tetragonal ZrO2 phases disappears or substantially disappears, thus the abrupt volume change is moderated or disappears.
[0181] Examples 7 and 8 are refractory materials with a relatively low content of SiO2, the main component of the glass phase. This is not intended to be theoretically limited, but rather to demonstrate that due to the effect of Y2O3, the reversible phase transition between the monoclinic and tetragonal crystal phases of ZrO2 disappears or largely disappears. This moderates the phase transition associated with rapid volume changes, resulting in good thermal cycling resistance even with a relatively low SiO2 content.
[0182] Figure 5A Photograph of the internal microstructure of a 93% by mass high-zirconia electrofused cast refractories after corrosion resistance evaluation. This refractories contains 0.24% by mass Y₂O₃. Figure 5B Photographs of the internal microstructure of the high-zirconia electrofused cast refractories involved in Example 1 after corrosion resistance evaluation (Y2O3 content = 5.67% by mass). As these photographs suggest, in refractories with a Y2O3 content exceeding 4% by mass, a network is easily formed between ZrO2 particles due to the high concentration of Y2O3 nodules formed by the crystallization of some Y2O3 contained in the glass phase or by the dissolution of Y2O3 dissolved in ZrO2. Therefore, as in Examples 7, 8, and 11, even with a relatively high porosity, the refractories exhibit corrosion resistance equal to or higher than that of the high-zirconia electrofused cast refractories with a ZrO2 content of 93% by mass.
[0183] In Examples 5 and 11, it is shown that the component (CaO or B2O3) that promotes the formation of zircon crystals is increased. However, if the Y2O3 content exceeds 4% by mass, even if zircon crystals are formed, the phase transition of the ZrO2 crystal from monoclinic to tetragonal crystals, which is accompanied by a sharp volume change, is moderated. Therefore, if the residual expansion rate is less than 2%, the resistance to thermal cycling is good.
[0184] As can be seen from Table 1, the high zirconia electrofused cast refractories of Examples 1 to 14, after being removed from the slowly cooled material, exhibit short or no cracks in appearance. Therefore, even if cracks occur, they can be partially removed, enabling mass production in industry. This process can suppress the opening of seams, suppress the residual expansion rate in response to thermal cycles, and enable the use of long-life refractories with high resistance to glass corrosion.
[0185] Table 3 shows refractory materials not included in this invention as comparative examples. The refractory materials involved in Comparative Examples 15-24 all exhibited poor quality in terms of the occurrence of cracking during manufacturing. Furthermore, some comparative examples also showed poor quality in terms of corrosion resistance and / or residual volume expansion rate after thermal cycling.
[0186] In the comparative examples, Comparative Examples 15-17 are refractory materials with relatively low Y2O3 content, and Comparative Example 15 is a composition corresponding to Patent Document 4 (Japanese Patent Publication No. 2013-514254). It is not intended to be theoretically limited, but rather to suggest that in these comparative examples, the relatively small amount of Y2O3 present results in a shift in the phase transition temperature of ZrO2 crystals from monoclinic to tetragonal towards a lower temperature. At this lower temperature, the viscosity of the glass phase is high, thus failing to mitigate the rapid volume change of ZrO2, causing the refractory to crack upon removal from the slowly cooled material.
[0187] In contrast, Comparative Example 19 is a refractory with a relatively high Y2O3 content. In this comparative example, Y2O3 is dissolved in ZrO2 crystals, and some of it is stabilized in cubic ZrO2, which may make it prone to cracking.
[0188] In the refractory materials involved in Comparative Examples 18 and 20-24, it was found that although the Y2O3 content was in the range of more than 4.0% to 9.0% by mass, at least one of the components SiO2, Al2O3, B2O3, Fe2O3, TiO2, MgO, CaO, K2O, and P2O5 was either too much or too little, resulting in cracking and other issues.
[0189] The refractory materials involved in these comparative examples are difficult to mass-produce industrially and may not be suitable for stable production.
[0190] Based on the above results, the high zirconia electrofused cast refractory of the present invention suppresses glass erosion caused by joint openings, exhibits high corrosion resistance, and demonstrates good resistance to thermal cycling, making it highly beneficial as a refractory for glass melting furnaces.
[0191] Furthermore, the high zirconia electro-casting refractories of the present invention are very advantageous for use in glass melting furnaces, but are not limited to glass melting furnace applications.
[0192] [Table 1]
[0193]
[0194] [Table 2]
[0195]
[0196] [Table 3]
[0197]
[0198] [Table 4]
[0199]
[0200] Explanation of reference numerals in the attached figures
[0201] 1. Samples for evaluating corrosion resistance
[0202] 2. Molten glass
[0203] 3 Crucibles for high-zirconia electro-cast refractories
[0204] 4. Zirconia electrofused cast refractories with 93% by weight after corrosion resistance test
[0205] 5. Refractory material involved in Example 1 after corrosion resistance test
Claims
1. High-zirconia electrofused cast refractories, among which, As a chemical composition, the total content of ZrO2 and HfO2 is greater than 80% and less than 92% by mass, Al2O3 is 0.2% to 3.0% by mass, SiO2 is 1.5% to 10% by mass, Na2O is 0.05% to 2.0% by mass, K2O is less than 1.0% by mass, B2O3 is 0% to 1.5% by mass, Y2O3 is greater than 4.0% and less than 9.0% by mass, the total content of MgO and CaO is 0.02% to 0.4% by mass, CaO is greater than 0.01% by mass, the total content of Fe2O3 and TiO2 is less than 0.5% by mass, and the content of P2O5 is less than 0.04% by mass. The ZrO2 and zircon raw materials used as raw materials for high-zirconia electrofused cast refractories contain 1-2% by mass of HfO2.
2. The high-zirconia electrofused cast refractories according to claim 1, wherein, As a chemical composition, the total content of ZrO2 and HfO2 is more than 80% by mass and less than 92% by mass, Al2O3 is 0.4% to 2.5% by mass, SiO2 is 1.5% to 7.0% by mass, Na2O is 0.3% to 1.8% by mass, K2O is less than 1.0% by mass, B2O3 is 0% to 1.0% by mass, Y2O3 is more than 4.0% by mass and less than 7.5% by mass, the total content of MgO and CaO is 0.02% to 0.4% by mass, CaO is more than 0.01% by mass, the total content of Fe2O3 and TiO2 is less than 0.5% by mass, and the content of P2O5 is less than 0.04% by mass.
3. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, The mass content of Y2O3 is 4.5 to 7.5% by mass.
4. The high-zirconia electrofused cast refractories according to claim 3, wherein, The mass content of Y2O3 is greater than 4.5% by mass and less than 6.0% by mass.
5. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, The mass content of SiO2 is 4.0 to 6.5%.
6. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, The mass content of Al2O3 is 0.5 to 1.2 by mass.
7. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, The Na2O content is 0.5–1.2% by mass.
8. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, The mass content of B2O3 is 0.01 to 0.6% by mass.
9. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, During the heating process from 200℃ to 1500℃, the expansion rate of the refractory reaches its maximum at temperatures between 1300℃ and 1500℃.
10. The high-zirconia electrofused cast refractories according to claim 1 or 2, wherein, During the cooling process from 1500℃, ZrO2 crystals do not shrink from tetragonal to monoclinic phase.
11. The high-zirconia electro-casting refractory according to claim 1 or 2, used in a glass melting furnace.
Citation Information
Patent Citations
Zirconia heat-resistant material for machine
JP1984131585A
Molten zirconia fireproofing material having high-temperature heat resistance and corrosion resistance and its production
JP1992042813A
Fused cast refractory products with high zirconia content
JP2005526683A
Refractories with a high zirconia content
JP2013514254A
High zirconia electrically melted cast refractory
JP2015040144A